8. Histopathological of Fabricius Bursa in the Broiler Chicken after Vaccination with Newcastle Disease Virus Vaccine - Ummu Balqis; Nurjannah Annah; Hamdani Budiman; Darmawi Darmawi; Cut Dahlia Iskandar; M. Hasan (Universitas Syiah Kuala, 2019)
The aim of this research was to determine an effect of Newcastle disease virus (NDV) vaccine to histopathologic on Fabricius bursa of broiler chicken at various age levels. Eighteen commercial DOC (Day Old Chick) were divided into 2 groups namely a control group that was given distilled water and a treatment group that was given NDV vaccine namely ND Lasota vaccine ocularly as much one drop per eye at day 3, then a booster dose in drinking water at day 13 was given. The bursa of Fabricius was collected from these chickens on the age of 14 days, 21 days, and 28 days after sacrificing the chickens through necropsied, then histopathological preparations are made using hematoxylin-eosin staining. The parameters observed were measured the number, diameter, and thickness of cortical of lymphoid follicles. Data were analyzed descriptively and quantitatively by unpaired t-test. The results of this research showed the NDV vaccine effects were not significantly different (P0.05) to the number and diameter of lymphoid follicles. In the treatment group, 14 days old broiler chickens had a decreased number of lymphoid follicles, while its diameter tends to grow and the thickness of cortex was also seemed unchanged compared with the control group. Then at the age of 21 days, the number, diameter, and thickness of cortex of lymphoid follicles tend to increase, while at 28 days diameter of lymphoid follicles tend to be slightly reduced, but the number and thickness tend to grow out of control. It was concluded that the NDV vaccine had a good effect on the Fabricius bursa of broiler chickens with increasing age, then histopathological preparations are made using hematoxylin-eosin staining.